The screening of phytochemical and antioxidant activity of agarwood leaves (Aquilaria malaccensis) from two sites in North Sumatra, Indonesia - Ridwanti Batubara; SURJANTO; T. ISMANELLY HANUM; ARBI HANDIKA; ODING AFFANDI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Batubara R, Surjanto, Hanum TI, Handika A, Afandi O. 2020. Phytochemical screening and antioxidant activity of agarwood leaves (Aquilaria malaccensis) from two sites in North Sumatra, Indonesia. Biodiversitas 21: 1588-1596. Agarwood of gaharu (Aquilaria malaccensis Lamk) has an antioxidant activity which can reduce free radicals. This research was conducted to analyze the chemical compounds of agarwood, and the antioxidant activities from two different grown sites, Laru, and Hutanabolon Village. Ethanol extracts of the agarwood leaves (EEAL) were obtained through maceration method. The phytochemical screening included the examination of secondary plant metabolites, while antioxidant activity was determined by free radicals scavenging activity against 1,1- diphenyl-2-picrylhydrazyl (DPPH). An observable parameter was the percentage of free-radical-reduction with different concentrations (40, 60, 80 and 100 ppm) and inhibitory concentrations (IC50) value by using regression equation. The phytochemical screening result showed that simplicia and EEAL from Laru grown site contained secondary plant metabolites, such as steroid/triterpenoids, flavonoids, saponins, and tannins, while simplicia leaves of agarwood from Hutanabolon grown site contained alkaloids, steroid/triterpenoids, saponins, and tannins, However, EEAL from Hutanabolon was found to only contain alkaloids. The f antioxidant activity of EEAL from Laru 27.887 ± 0.560 ppm was not different from Hutanabolon 27.807 ± 4.630 ppm. The EEAL from both Laru and Hutanabolon had a very strong antioxidant activity.